Effect of Liquid Media Composition on Alpha-Glucosidase Inhibitory Activity from Aspergillus elegans SweF9 - Hani Mulyani; Rizna Triana Dewi; Euis Filailla; Nina Artanti (Research Center for Chemistry - LIPI, 2020)
This study aims to determine the effect of liquid media composition on the inhibitory activity of Î±-glucosidase from endophytic fungus Aspergillus elegans SweF9 isolated from seaweed (Macroalgae Euchema sp). Fermentation was carried out in three types of liquid media, namely: potato dextrose broth (PDB), potato malt peptone (PMP), and Czapek-dox broth (CDB), which was incubated for 10 days at room temperature, with static conditions. Ethyl acetate solvents were used to extract active metabolites from fungal biomass and filtrate from each media. Antidiabetic activity was measured based on inhibition of enzyme Î±-glucosidase. The results showed that filtrate extract of A. elegans SweF9 which was cultured on the media PDB showed highest inhibitor activity to the Î±-glucosidase enzyme with an IC50 value of 1.74 Âµg / mL compared to other extracts. Based on these results, the PDB media is an appropriate medium for culturing A. elegans SweF9Â to produces secondary metabolites that can be used as a new source of antidiabetic agents.